Thermochronological insights into the thermotectonic evolution of Mishmi hills across the Dibang Valley, NE Himalayan Syntaxis. (1st April 2020) - Salvi, Dnyanada; Mathew, George; Kohn, Barry; Pande, Kanchan; Borgohain, Biraj
Graphical abstract: Highlights: First multi-thermochronometry results from Dibang Valley, Eastern Himalaya. Frontal zone cooled below 350 °C ca. 16 Ma, east of Hunli cooled ca. 16 - 13 Ma. Duplex initiated close to ~8-9 Ma. LHS duplexing continued into Mid Pliocene. Detachment depth ~5 km beneath Hunli. Maximum height ~6 km above Hunli window. Abstract: Eastern Himalayan Syntaxis (EHS) that forms the northeastern termination of the Himalaya consists of three broad zones; Namche Barwa massif, Siang antiform and Mishmi Hills. The present work provides new in-situ apatite fission track (AFT), zircon (U-Th)/He (ZHe) and 40 Ar/ 39 Ar multi-thermochronometric ages across the Dibang valley in the Mishmi hills. The study constrains the structure, emplacement time of major thrusts and initiation of Lesser Himalayan Duplex (LHD). Biotite 40 Ar/ 39 Ar ages of the Lohit batholith suggest late Oligocene cooling. ZHe ages indicate late Miocene (~8–9 Ma) foreland directed duplex initiation in the Dibang valley. The AFT cooling ages (~5–3 Ma) suggest LHD continued into Mid Pliocene. Confined track lengths and thermal modelling indicate that the northeastern samples from the study area underwent a phase of rapid exhumation around 10 Ma, followed by slow cooling. It is in contrast to the south-western samples from the Dibang valley that have cooled and uplifted rapidly only after around 4 Ma, due to accelerated phase of LHD. Our 3D thermo-kinematic modelling of the data indicates less mass removal around Hunli than other parts of Dibang valley. The result is in contrast to previously estimated ~16 km uplift near Hunli and mass removal. AFT ages from the Hunli window indicate that the region witnessed modest uplift of ~4–5 km since ca. 4 Ma. Brittle duplexing of the lower LHS at Hunli and Mayodia caused the warping of the overlying litho-units. Hunli duplex alone accommodated ~86% of the total shortening.